Analyses of Twelve New Whole Genome Sequences of Cassava Brown Streak Viruses and Ugandan Cassava Brown Streak Viruses from East Africa: Diversity, Supercomputing and Evidence for Further Speciation - Ndunguru, Joseph; Sseruwagi, Peter; Tairo, Fred; Stomeo, Francesca; Maina, Solomon; Djikeng, Appolinaire; Kehoe, Monica; Boykin, Laura M. (Public Library of Science, 2015)
Cassava brown streak disease is caused by two devastating viruses, Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) which are frequently found infecting cassava, one of sub-Saharan Africa’s most important staple food crops. Each year these viruses cause losses of up to $100 million USD and can leave entire families without their primary food source, for an entire year. Twelve new whole genomes, including seven of CBSV and five of UCBSV were uncovered in this research, doubling the genomic sequences available in the public domain for these viruses. These new sequences disprove the assumption that the viruses are limited by agro-ecological zones, show that current diagnostic primers are insufficient to provide confident diagnosis of these viruses and give rise to the possibility that there may be as many as four distinct species of virus. Utilizing NGS sequencing technologies and proper phylogenetic practices will rapidly increase the solution to sustainable cassava production.